TARGETS AND MOLECULAR MECHANISM OF DIOSCIN AGAINST HUMAN BREAST CANCER: A SYSTEMATIC IN SILICO ANALYSIS - S.R. YOGARAJ; VEERANARAYANAN SURYA AATHMANATHAN; MUTHUKALINGAN KRISHNAN; KUMPATI PREMKUMAR (The Bioscan, 2020)
Dioscin is a natural glycoside predominantly present in many plants. It has been shown to possess anti-proliferative effect on variety of human cancer cells in vitro and in vivo. And recent studies reported that Dioscin could reverses TGF-ß1 induced epithelial mesenchymal transition (EMT) in cancer cells. However, the mechanism by which Dioscin can suppresses EMT and pathway involved in Breast cancer is still not clear. Both genomic and proteomic analysis was carried out to understand the binding mechanism of Dioscin with breast cancer targets. Target network analysis and GO were carried out to find the interaction of the important pathway proteins and molecular docking, ADME were carried out to find the binding affinity and pharmacokinetic properties of the Dioscin. The results shows that Dioscin has good binding affinity with three major pathway proteins with significant docking score and also it obeys all the criteria of ADME properties. The network and GO analysis also shows the higher interaction of Dioscin with major three pathway proteins (SMAD2, PIK3 and p38MAPK). The overall results of the study suggested that Dioscin have the potential to inhibit the breast cancer target by which it regulates the apoptosis and DNA damage repair mechanism.